Crowned dens syndrome. Issue 1 (24th November 2017) - Ledingham, David; Cappelen-Smith, Cecilia; Cordato, Dennis
Abstract : Crowned dens syndrome is a rare presentation of calcium pyrophosphate deposition disease. It is characterised by severe occipital pain and neck stiffness. Acute presentations are typically accompanied by fever and an inflammatory response and hence can be misdiagnosed as polymyalgia rheumatica or meningitis. Chronic relapsing presentations may be misdiagnosed as cervicogenic neck pain or occipital neuralgia. We present a patient who presented with a chronic relapsing form of crowned dens syndrome and discuss the epidemiology, typical presentation and management of this eminently treatable condition.